2008
DOI: 10.1128/iai.00305-08
|View full text |Cite
|
Sign up to set email alerts
|

Cif Is Negatively Regulated by the TetR Family Repressor CifR

Abstract: We previously reported that the novel Pseudomonas aeruginosa toxin Cif is capable of decreasing apical membrane expression of the cystic fibrosis transmembrane conductance regulator (CFTR). We further demonstrated that Cif is capable of degrading the synthetic epoxide hydrolase (EH) substrate S-NEPC [(2S,3S)-trans-3-phenyl-2-oxiranylmethyl 4-nitrophenol carbonate], suggesting that Cif may be reducing apical membrane expression of CFTR via its EH activity. Here we report that Cif is capable of degrading the xen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 53 publications
4
57
0
1
Order By: Relevance
“…Interestingly, we were unable to detect significant aCif catalysis of epibromohydrin, a substrate hydrolyzed by P. aeruginosa Cif and originally used to characterize its EH activity (27,46). Direct side-by-side epibromohydrin hydrolysis assays confirmed the discrepancy (data not shown).…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…Interestingly, we were unable to detect significant aCif catalysis of epibromohydrin, a substrate hydrolyzed by P. aeruginosa Cif and originally used to characterize its EH activity (27,46). Direct side-by-side epibromohydrin hydrolysis assays confirmed the discrepancy (data not shown).…”
Section: Resultssupporting
confidence: 50%
“…Gene expression was monitored by qRT-PCR in WT A. nosocomialis cultured in the absence or presence of three epoxide compounds. One of these was epibromohydrin, a known activator of cif transcription in P. aeruginosa (46). However, because our substrate profiling indicated that aCif has a strong preference for (S)-styrene oxide (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…E. coli expressing PleD R148A was obtained from Urs Jenal (University of Basel, Switzerland), and the protein was purified as described (15,31). Purification of LapD6H and variants from E. coli was performed as previously described (32), with the addition of 1% Triton to all buffers. Protein purifications ranged from 79% to 96% purity, as determined by SDS PAGE gel staining and densitometry, and molar concentrations of each protein were corrected according to relative purity before all assays.…”
Section: Deletion and Complementation Of Lapdmentioning
confidence: 99%